OPTIMASI MICROSOFT EXCEL 2016 DALAM PEMBUATAN LAPORAN PENILAIAN AKHIR SISWA PADA PENGURUS DAN STAF PENGAJAR PAUD EDELWEISS - Destiana, Henny; Kusumo, Aryo Tunjung; Agustini, Fajar; Widanengsih, Euis (Asosiasi Dosen Muda Indonesia, 2024)
The community service activity at PAUD Edelweiss aims to enhance the skills of administrators and teaching staff in using Microsoft Excel to support administrative tasks. The training was designed using lectures, tutorials, and hands-on practice, providing participants with both theoretical understanding and practical skills. The material covered includes creating tables, utilizing formulas, and preparing reports. Evaluations showed significant improvements in participants' abilities, leading to increased work efficiency and operational effectiveness. This program not only benefits individuals but also contributes to improving the quality of technology-based education at PAUD Edelweiss, serving as a strategic step toward digitalizing educational administration.